Synthesis of Alkanethiolate-Capped Metal Nanoparticles Using Alkyl Thiosulfate Ligand Precursors: A Method to Generate Promising Reagents for Selective Catalysis - San, Khin Aye (Nanomaterials (Basel), 2018)
Evaluation of metal nanoparticle catalysts functionalized with well-defined thiolate ligands can be potentially important because such systems can provide a spatial control in the reactivity and selectivity of catalysts. A synthetic method utilizing Bunte salts (sodium S-alkylthiosulfates) allows the formation of metal nanoparticles (Au, Ag, Pd, Pt, and Ir) capped with alkanethiolate ligands. The catalysis studies on Pd nanoparticles show a strong correlation between the surface ligand structure/composition and the catalytic activity and selectivity for the hydrogenation/isomerization of alkenes, dienes, trienes, and allylic alcohols. The high selectivity of Pd nanoparticles is driven by the controlled electronic properties of the Pd surface limiting the formation of Pd–alkene adducts (or intermediates) necessary for (additional) hydrogenation. The synthesis of water soluble Pd nanoparticles using ω-carboxylate-S-alkanethiosulfate salts is successfully achieved and these Pd nanoparticles are examined for the hydrogenation of various unsaturated compounds in both homogeneous and heterogeneous environments. Alkanethiolate-capped Pt nanoparticles are also successfully synthesized and further investigated for the hydrogenation of various alkynes to understand their geometric and electronic surface properties. The high catalytic activity of activated terminal alkynes, but the significantly low activity of internal alkynes and unactivated terminal alkynes, are observed for Pt nanoparticles.